Hybrid geographies natures, cultures, spaces - Whatmore, Sarah (London SAGE, 2002)
Case studies are used to demonstrate the argument that nature and culture are intimately and variously interrelated. The author draws upon highly topical theories informed by work in geography, feminist theory and environmental ethics and science.
Includes bibliographical references and index.
Keywords: Human ecology; Human beings -- Effect of environment on; Electronic books